Culinary Tourism “Nasi Sex” on Gandoriah Beach, Pariaman City: Mother Ina’s Pondok Salero (1987-2020) - Putri Amelia, Gheby; Zulfa, Zulfa; Kaksim, Kaksim (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study discusses the History and Impact of Covid-19 on Culinary Tourism Nasi Sek at Gandoriah Beach, Pariaman City: Pondok Salero Ibu Ina (1987-2020). The problems of this research are: how was the early history of selling Nasi Sek Pondok Salero Ibu Ina as a culinary tour at Gandoriah Beach, Pariaman City (1987-2020), and how did the Covid-19 outbreak affect Nasi Sek Pondok Salero Ibu Ina. The purpose of this study is to determine the early history of selling Nasi Sek Pondok Salero Ibu Ina as a culinary tour at Gandoriah Beach, Pariaman City (1987-2020), and to determine the effect of the Covid-19 outbreak on Nasi Sek Pondok Salero Ibu Ina. The research method used in this study is the Historical Research Method, this method is divided into four stages: 1) Heuristics, 2) Source Criticism, 3) Interpretation, 4) Historiography. Based on the results of the study, it can be concluded that: 1) the early history of starting to sell and the development of Nasi Sek Pondok Salero Ibu Ina as a culinary tour at Gandoriah Beach, Pariaman City (1987-2020). Because Nasi Sek Pondok Salero Ibu Ina is often visited by visitors from various regions outside Pariaman City and this Nasi Sek is also a typical culinary of Pariaman City to be tasted. 2) The Impact of the Covid-19 Outbreak on Nasi Sek Pondok Salero Ibu Ina. Because the impact of the Covid-19 outbreak has been felt by various groups in society which has caused economic life to decline.